Canary in the coal mine—Initial reports of thermal injury secondary to electronic cigarettes. Issue 3 (May 2017) - Bauman, Zachary M.; Roman, Jordan; Singer, Matthew; Vercruysse, Gary A.
Abstract: The use of electronic cigarettes has become increasingly popular with claims suggesting healthier alternatives to tobacco cigarettes. However, research regarding the safety of such devices has been limited to an analysis of the inhaled vapor and the short and long-term effects on the body. A lesser recognized risk of electronic cigarette use is that of lithium-ion battery failure causing ignition, leading to severe thermal injury. Such incidents have been reported in the media but with inconsistencies from a lack of focus on the injuries sustained and a cause of ignition. The cases presented here are among the first recognized thermal injuries sustained from electronic cigarette lithium-ion battery failure, the potential rationale for these failures, and a need for increased awareness of the safety hazards of these devices.